2022
DOI: 10.1039/d1cc06520c
|View full text |Cite
|
Sign up to set email alerts
|

RBD conjugate vaccine with a built-in TLR1/2 agonist is highly immunogenic against SARS-CoV-2 and variants of concern

Abstract: The coronavirus 2019 (COVID-19) pandemic is causing serious impact in the world, safe and effective vaccines and medicines are the best method to combat the disease. The receptor-binding domain (RBD)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Female BALB/c mice aged 6 weeks were vaccinated on days 1, 15, and 29 for subcutaneous injection (200 mL per mouse), and the sera were collected on days 14, 28, and 42 to evaluate the antibody immune responses including enzyme linked immunosorbent assay (ELISA), fluorescence-activated cell sorting (FACS) analysis, and complement-dependent cytotoxicity (CDC) assay (48)(49)(50). In addition, the spleens from mice were collected on days 42 to evaluate the cellular immune responses including cytotoxic T lymphocyte (CTL) assay, intracellular cytokine staining (ICS) assay, and enzyme-linked immunospot (ELISpot) assay (51)(52)(53)(54). All mice used in the experiments were purchased and bred in the Laboratory Animal Centre of Huazhong Agriculture University, and the experiments were conducted strictly in accordance with the principles of welfare and ethics of medical laboratory animals.…”
Section: Vaccine Design and Immunizationmentioning
confidence: 99%
“…Female BALB/c mice aged 6 weeks were vaccinated on days 1, 15, and 29 for subcutaneous injection (200 mL per mouse), and the sera were collected on days 14, 28, and 42 to evaluate the antibody immune responses including enzyme linked immunosorbent assay (ELISA), fluorescence-activated cell sorting (FACS) analysis, and complement-dependent cytotoxicity (CDC) assay (48)(49)(50). In addition, the spleens from mice were collected on days 42 to evaluate the cellular immune responses including cytotoxic T lymphocyte (CTL) assay, intracellular cytokine staining (ICS) assay, and enzyme-linked immunospot (ELISpot) assay (51)(52)(53)(54). All mice used in the experiments were purchased and bred in the Laboratory Animal Centre of Huazhong Agriculture University, and the experiments were conducted strictly in accordance with the principles of welfare and ethics of medical laboratory animals.…”
Section: Vaccine Design and Immunizationmentioning
confidence: 99%
“…Pam3CSK4, TLR1/2 agonist, has been studied in combination with protein adjuvants as alternative vaccine for SARS-CoV-2. Studies about the vaccine showed that Pam3CSK4 protects organism against SARS-CoV-2 virus ( Zhou et al, 2022 ).…”
Section: Tlrs Sensing Of Sars-cov-2mentioning
confidence: 99%
“…In addition, we also investigated potent COVID-19 subunit vaccines using RBD as the protein antigen. 13 , 14 However, few studies have systematically compared these S subunits as vaccine antigens in immunological evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a stabilized prefusion form of the S protein (S-trimer) was achieved by adding two stabilizing proline mutations in the C-terminal S2 fusion in previous research. , Given their indispensable functions in viral infection, the S-trimer, , S-ECD (extracellular domain), S1, , and RBD , are ideal targets for developing subunit vaccines against SARS-CoV-2 and its variants. In addition, we also investigated potent COVID-19 subunit vaccines using RBD as the protein antigen. , However, few studies have systematically compared these S subunits as vaccine antigens in immunological evaluation.…”
Section: Introductionmentioning
confidence: 99%